Analysis of Pseudomonas aeruginosa Conditional Psl Variants Reveals Roles for the Psl Polysaccharide in Adhesion and Maintaining Biofilm Structure Postattachment - Ma, Luyan (American Society for Microbiology, 2006)
The ability to form biofilms in the airways of people suffering from cystic fibrosis is a critical element of Pseudomonas aeruginosa pathogenesis. The 15-gene psl operon encodes a putative polysaccharide that plays an important role in biofilm initiation in nonmucoid P. aeruginosa strains. Biofilm initiation by a P. aeruginosa PAO1 strain with disruption of pslA and pslB (ΔpslAB) was severely compromised, indicating that psl has a role in cell-surface interactions. In this study, we investigated the adherence properties of this ΔpslAB mutant using biotic surfaces (epithelial cells and mucin-coated surfaces) and abiotic surfaces. Our results showed that psl is required for attachment to a variety of surfaces, independent of the carbon source. To study the potential roles of Psl apart from attachment, we generated a psl-inducible P. aeruginosa strain (Δpsl/p(BAD)-psl) by replacing the psl promoter region with araC-p(BAD), so that expression of psl could be controlled by addition of arabinose. Analysis of biofilms formed by the Δpsl/p(BAD)-psl strain indicated that expression of the psl operon is required to maintain the biofilm structure at steps postattachment. Overproduction of the Psl polysaccharide led to enhanced cell-surface and intercellular adhesion of P. aeruginosa. This translated into significant changes in the architecture of the biofilm. We propose that Psl has an important role in P. aeruginosa adhesion, which is critical for initiation and maintenance of the biofilm structure.